The Political Economy of Rentier States: Understanding Barriers on ‎Economic Reform and Integration in GCC States - Muhammad Khairil Zaki Al-Asyura; M. Hamdan Basyar (Universitas Muhammadiyah Jember, 2022)
The GCC states’ high dependence on the hydrocarbon sector does not reflect a sustainable ‎economy. Therefore, it is demanded that those states reform the economic system that has long ‎been preserved and accelerate economic integration in the region to reduce ‎oil dependence. This article aims to analyze the hindrances to the economic reform ‎program and the intention to achieve economic integration within the rentier state in the Arab ‎Gulf states. This article uses a qualitative method through an explanatory and descriptive ‎approach to elaborate on the issues. This study indicates that a comprehensive economic ‎reform in GCC countries is hard to implement due to the existing political structure and socio-‎cultural conditions. Were to reform the economic system totally, rulers would have a dilemma regarding the regime's sustainability. Meanwhile, the move towards economic integration within the GCC countries remains unachievable due to such unresolved issues as mistrust among member countries, powerless GCC’s structural organization, and the lack of ‎interdependency-complex in pursuing wealth and prosperity